PENGARUH NAUNGAN TERHADAP KANDUNGAN NITROGEN DAN PROTEIN DAUN SERTA PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (The Effect of Shading to Nitrogen and Protein Contents, The Growth and Yield of Soybean Plants) - Nerty Soverda; . Evita; . Gusniwati (Bioplantae, 2012)
One way to improve the productivity of soybean grown as an intercropping plant in the standing area is to develop soybean varieties that are tolerant to shade. This experiment aimed to discover the physiological characteristics in soybean varieties that are tolerant to shade.The results showed that the significant physiological characteristics that determine the level of the soybean tolerance to shade are nitrogen and protein contents.The increasing of nitrogen and protein contents was higher in the tolerant varieties than those of sensitive varieties. Shade treatments affected seed weight. The soybean yield on the 50% shade decreased by 23.11% in the tolerant varieties, and about 27.63% decreased in the sensitive varieties. The yield decrease was lower in tolerant varieties compared to the sensitive varieties. This result was supported by the lower reduction in empty pods.Mechanism of tolerance to shade on soybean plant is characterized by the increase of nitrogen and protein contents. In addition, higher yields on tolerant varieties supported by high pods contain and low empty pods.Key words: Soybean, nitrogen and protein contents.